Alkaline water hydrogen production anode and preparation method thereof

Through the coating and sintering process of porous nickel slurry on nickel-based materials, a high-active and stable three-dimensional nickel electrode was prepared, which solved the problem of nickel particles agglomeration during the complex preparation and activation of Rainey nickel electrodes, and achieved the improvement of electrode activity and stability and the simplification of the preparation process.

CN119685849APending Publication Date: 2025-03-25SHANGHAI YUXIN JINYUE ENERGY TECHNOLOGY CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411925547.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-25
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

The existing Rainey nickel electrode preparation process is complex, the structure is difficult to control, and the problem of nickel particles agglomeration during activation will be caused.

Method used

The slurry is prepared by porous nickel, coated on the surface of nickel mesh, nickel felt, nickel foam or nickel-plated metal porous plate/belt by scraper method, and a three-dimensional nickel electrode for electrolyzed hydrogen is produced through an appropriate sintering process.

Benefits of technology

The obtained electrode has high electrode activity and stability, simplifies the preparation process, reduces costs, and does not require activation treatment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119685849A_ABST
    Figure CN119685849A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of electrochemistry, and particularly relates to an alkaline water hydrogen production anode and a preparation method thereof. The preparation method mainly comprises the following steps: preparing slurry, preparing a plain blank, discharging glue and sintering. According to the preparation method, three-dimensional porous nickel is prepared into slurry, and the three-dimensional porous nickel is prepared into the three-dimensional nickel electrode (a nickel net, a nickel felt, foamed nickel or a nickel-plated metal porous plate / strip is used as a base material) through a slurry / roasting process. The three-dimensional integrated self-supporting electrode structure can enhance the bonding strength among the components, promote the transfer of charges on an interface, and ensure high activity and high stability. In order to restrain the influence of bubbles under the working condition of high current density, the porosity of the catalyst layer can be increased, so that effective bubble management is achieved, and disturbance and damage to the catalyst layer in the bubble desorption process are reduced. And the three-dimensional porous structure can reduce the use amount of nickel and reduce the cost.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of electrochemistry, and in particular relates to an alkaline water hydrogen production anode and a preparation method thereof. Background Art

[0002] Electrodes play a vital role in hydrogen production electrolyzers. They are the place where electrochemical reactions occur and the core area of ​​hydrogen generation. At the same time, the catalytic performance of the electrode also determines the efficiency of hydrogen production. Efficient electrodes can reduce energy consumption and increase the rate of hydrogen production. In the process of hydrogen production by alkaline water electrolysis, there are many types of electrode catalysts, including precious metal-based catalysts (such as platinum, palladium, gold, silver, etc.) and non-precious metal-based catalysts (such as iron, cobalt, nickel, etc.), as well as non-metallic catalysts (such as carbon materials). The selection and optimization of these catalysts are key factors in improving hydrogen production efficiency and reducing costs. Through the design of electrodes and material selection, the overall performance and economic benefits of the hydrogen production system can be effectively improved. Electrodes for hydrogen production by alkaline water electrolysis are usually nickel-based because nickel can withstand high temperatures, alkali corrosion and has relatively low costs. Nickel-based electrodes are mostly based on pure nickel mesh, nickel foam, etc., and catalysts are coated by spraying, rolling, chemical plating and other processes to improve electrolysis efficiency. Catalysts are mostly nickel-based catalysts represented by Raney nickel, or precious metal catalysts. Raney Nickel is an alloy composed of nickel and aluminum. Usually, nickel and aluminum are mixed and fused in a certain proportion to form an alloy, and then fine particles are obtained by quenching and crushing. Generally, 80 / 20 Raney Nickel is used, that is, 80% (mass ratio) nickel and 20% (mass ratio) aluminum. The spraying process is to use a certain heat source (such as plasma arc, combustion flame, etc.) to heat the nickel-aluminum alloy powder to a molten or semi-molten state. These molten or semi-molten particles are driven by high-speed airflow and hit the pre-treated nickel mesh surface. Due to the high temperature and high speed of the particles, they will quickly flatten, solidify and form mechanical and metallurgical bonds with the surface of the nickel mesh when they hit the surface. During the spraying process, spraying parameters such as spraying distance, spraying angle, spraying speed, etc. need to be precisely controlled to ensure the quality and performance of the coating. The general spraying thickness is 240-300g / m 2 . After spraying Raney nickel on the nickel mesh, the high nickel content and low aluminum content can ensure that the nickel in the molten Raney nickel can effectively combine with the wire mesh. The aluminum in the Raney nickel will randomly appear on the sprayed coating. At this time, the sprayed nickel mesh needs to be activated with sodium hydroxide solution. The so-called activation treatment is to react the aluminum in the Raney nickel. As the aluminum in the coating is reacted, the surface of the coating will show a bumpy shape, which greatly increases the specific surface area of ​​the electrode (the average specific surface area of ​​commercial Raney nickel is about 100m 2 / g), thereby improving the electrolysis efficiency. Different electrode structures have an impact on their strength and activity. After activation, the strength will decrease. In addition, there is aluminum between the nickel and the nickel mesh after spraying, which causes the nickel to fall off during activation. Most research on hydrogen production by electrolysis of water is based on powder catalysts or small-area integrated electrodes, and is mainly synthesized through precipitation, water / solvent thermal, electrodeposition and other techniques. Although these methods can meet the size requirements of centimeter-level electrodes in the laboratory, it is difficult to uniformly prepare large-size electrodes of meter-level for industrial alkaline electrolyzers. Other methods such as chemical deposition and electrochemical deposition have poor bonding between their electrode structures and catalyst particles and between the catalyst layer and substrate, which leads to local shedding during the operation of the electrolyzer, so they are still in the laboratory stage.

[0003] With the continuous development of the renewable energy hydrogen production industry, the requirements for large-scale electrolyzer equipment are getting higher and higher. The simple superposition of small chambers will cause the length of the electrolyzer to be too long, which is not conducive to the assembly and installation of the electrolyzer. There are also many problems such as the sinking of the middle of the electrolyzer. Therefore, improving the current density by optimizing the catalyst is a feasible path. According to Faraday's law, the mass of the substance undergoing chemical changes on the electrode interface is proportional to the amount of electricity passed in. The key to increasing the current density is to increase the rate of electrochemical reactions on the catalyst surface under a given small chamber voltage, which depends on two aspects of the catalyst's characteristics, namely the number of catalytic sites and the intrinsic activity of the catalytic sites. The porous structure of the Raney nickel catalyst is to further increase its specific surface area, so that there are more sites to participate in the water electrolysis reaction under a given small chamber voltage, and the current density will be further improved.

[0004] Although there are many new composite catalysts, such as nickel-molybdenum, nickel-iron, etc., it is difficult to use them in actual electrolytic cells because the electrochemical corrosion caused by the contact between two different metals and being in the electrolyte at the same time leads to the destruction of the catalytic layer structure.

[0005] At present, a large amount of research work is devoted to developing catalysts with high intrinsic activity and durability under mild conditions. By adjusting the electronic structure to optimize the adsorption energy of the reaction intermediate, on the one hand, the intrinsic activity can be improved, such as heterogeneous atom doping, heterogeneous structure design, amorphization and alloying, etc. For example, in the patent with publication number CN118480810A, in order to reduce the polarization of the cathode, one or more single-atom catalysts anchored by defect-rich NiPS nanosheets are prepared by chemical solution method, and noble metals are introduced into the catalytic layer. The noble metal-based materials (Pt, etc.) have high HER catalytic activity, but they have the problems of resource scarcity and high cost, which limits their large-scale application. In the patent with publication number CN118639258A, in order to improve the activity of the electrode, a nickel-molybdenum alloy electrode is sprayed on a nickel mesh using a plasma spraying device. As is well known, the molybdenum particles in the electrode will form a primary cell with the nickel particles and the nickel mesh substrate in contact, resulting in the attenuation of the electrode performance. In the patent with publication number CN118653173A, thermal spraying is also used to form a nickel-molybdenum first catalytic layer and a second layer of aluminum-rhenium-doped nickel-molybdenum-iron alloy powder on a nickel mesh. Not only will a primary battery of different metal powders / substrates be formed, affecting the life of the electrode, but activation dealumination is also required, resulting in difficulty in repeating the electrode composition and structure. In addition, hydrogen will be released during the dealumination process, greatly increasing the safety requirements for production.

[0006] Therefore, based on this, the technical solution of the present invention is proposed. Summary of the invention

[0007] In order to solve the problem that the commonly used Raney nickel electrode preparation process is complicated, the structure is not easy to control, and the activation process will bring the problem of nickel particle agglomeration. The present invention adopts porous nickel to prepare slurry, and the slurry is coated on the surface of nickel mesh, nickel felt, foamed nickel or nickel-plated metal porous plate / belt by a scraper method, and then a three-dimensional nickel electrode for electrolyzing water to produce hydrogen is made through an appropriate sintering process. The electrode prepared by controlling the viscosity of the slurry and the sintering process has high porosity and good bonding with the nickel mesh at the same time. Compared with traditional Raney nickel electrodes, the electrode obtained by the present invention has high electrode activity and stability. And by selecting suitable nickel powder and adapted process, the use amount of nickel powder is reduced, and it is not necessary to go through the activation process, simplifying the preparation process of the electrode, and reducing the preparation cost of the electrode.

[0008] Specifically, the present invention provides a method for preparing an alkaline water hydrogen production anode, comprising the following steps:

[0009] (1) mixing ultrafine porous nickel powder and methyl cellulose to prepare a slurry;

[0010] (2) The substrate is cleaned and dried, and then the slurry is coated on one side of the substrate (such as Figure 1 Finally, drying is performed to obtain a raw embryo;

[0011] (3) heating the green embryo to remove binder and obtain a pretreated green embryo;

[0012] (4) Sintering the pretreated blank to obtain the alkaline water hydrogen production anode.

[0013] Preferably, in step (1), the particle size of the ultrafine porous nickel powder is 2.1 to 2.8 μm.

[0014] Preferably, in step (1), in the slurry, the mass fraction of the ultrafine porous nickel powder is 15-70%, and the mass fraction of the methyl cellulose is 3-4%;

[0015] And / or, the viscosity of the slurry is 30-35 Pa·S. It should be noted that, because the viscosity of the slurry has a great influence on the coating process, the viscosity of the slurry in the present invention is selected to be 30-35 Pa·S, and the proportion of methyl cellulose in the slurry is 3-4%. The role of methyl cellulose is to bond and suspend the nickel powder in the slurry, and to adjust the process properties of the slurry such as viscosity, rheology, and thixotropy. During the sintering process, the methyl cellulose will be completely volatilized, and the nickel powder will be sintered at high temperature to form a metal network structure.

[0016] Among them, ultra-fine porous nickel powder can be selected as Type 255 TM 、Type 240 TM And other types of porous nickel powder.

[0017] Preferably, in step (2), the substrate is one of nickel mesh, nickel felt, nickel foam, perforated nickel belt, nickel-plated metal porous plate, and nickel-plated metal porous belt.

[0018] Preferably, in step (2), the drying method is: drying in an air atmosphere at 150-160° C. for 10-15 min.

[0019] Preferably, in step (3), the heating method is: in an air atmosphere, the temperature is raised to 350-360° C. at a rate of 60° C. / h, and kept warm for 30-40 min.

[0020] Preferably, in step (4), the sintering method is: sintering at 700-1350° C. for 10-15 min in an inert atmosphere.

[0021] Preferably, the inert atmosphere is a mixed gas of hydrogen and nitrogen, and the volume ratio of hydrogen to nitrogen is 3:100.

[0022] Based on the same technical concept, the present invention further provides an alkaline water hydrogen production anode obtained by the above preparation method.

[0023] The beneficial effects of the present invention are:

[0024] The preparation method of the present invention is to prepare the three-dimensional porous nickel into a slurry, and prepare the three-dimensional porous nickel into a three-dimensional nickel electrode (nickel mesh, nickel felt, nickel foam, or nickel-plated metal porous plate / belt as a substrate) through a slurry / calcination process. The three-dimensional integrated self-supporting electrode structure can enhance the bonding strength between the components, promote the transfer of charge on the interface, and ensure high activity and high stability. In order to suppress the influence of bubbles under high current density conditions, the porosity of the catalyst layer can be increased, thereby achieving effective bubble management and reducing the disturbance and damage to the catalyst layer during bubble desorption. Moreover, the three-dimensional porous structure can reduce the amount of nickel used and reduce costs. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0026] Figure 1 is a schematic diagram of electrode coating.

[0027] Figure 2 This is a graph of slotting test results. DETAILED DESCRIPTION

[0028] To make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be described in detail below. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other implementation methods obtained by ordinary technicians in this field without creative work belong to the scope of protection of the present invention.

[0029] Example 1

[0030] This embodiment provides a method for preparing an alkaline water hydrogen production anode, comprising the following steps:

[0031] (1) Commercially available ultra-fine porous nickel powder Type 255 TM (particle size of 2.2-2.8 μm) and methyl cellulose are mixed and prepared into a slurry according to a conventional method; wherein the mass fraction of nickel powder in the slurry is 54%, the mass fraction of methyl cellulose is 3%, and the viscosity of the slurry is 30 Pa·S;

[0032] (2) After a nickel mesh (46 mesh, stretched) was cleaned and dried by ultrasonic wave, an excess amount of the slurry was manually coated, and then the slurry was coated on one side of the nickel mesh by casting, and then placed in an oven at 150° C. in an air atmosphere for 10 min to obtain a blank (thickness of 0.73 mm);

[0033] (3) In an air atmosphere, the green embryo is heated to 350° C. at a rate of 60° C. / h and kept at this temperature for 30 minutes for debinding to obtain a pretreated green embryo;

[0034] (4) The pretreated blank is placed in an inert atmosphere for reduction high-temperature sintering, wherein the composition of the inert atmosphere is H2 / N2=3%, the sintering temperature is 700°C, and the insulation time is 10 minutes. After completion, an alkaline water hydrogen production anode is obtained.

[0035] Example 2

[0036] This embodiment provides a method for preparing an alkaline water hydrogen production anode, comprising the following steps:

[0037] (1) Commercially available ultra-fine porous nickel powder Type 255 TM (particle size of 2.2-2.8 μm) and methyl cellulose are mixed and prepared into a slurry according to a conventional method; wherein the mass fraction of nickel powder in the slurry is 54%, the mass fraction of methyl cellulose is 3%, and the viscosity of the slurry is 30 Pa·S;

[0038] (2) After the nickel mesh (46 mesh, stretched) was cleaned and dried by ultrasonic wave, an excess amount of the slurry was manually coated, and then the slurry was coated on one side of the nickel mesh by casting, and then placed in an oven at 150° C. in an air atmosphere for 10 min to obtain a blank (thickness of 0.74 mm);

[0039] (3) In an air atmosphere, the green embryo is heated to 350° C. at a rate of 60° C. / h and kept at this temperature for 30 minutes for debinding to obtain a pretreated green embryo;

[0040] (4) The pretreated blank is placed in an inert atmosphere for reduction high-temperature sintering, wherein the composition of the inert atmosphere is H2 / N2=3%, the sintering temperature is 1350°C, and the insulation time is 10 minutes. After completion, an alkaline water hydrogen production anode is obtained.

[0041] Example 3

[0042] This embodiment provides a method for preparing an alkaline water hydrogen production anode, comprising the following steps:

[0043] (1) Commercially available ultrafine porous nickel powder Type 240 TM(particle size of 2.1-2.2 μm) and methyl cellulose are mixed and prepared into a slurry according to a conventional method; wherein the mass fraction of nickel powder in the slurry is 46%, the mass fraction of methyl cellulose is 3%, and the viscosity of the slurry is 30 Pa·S;

[0044] (2) After a nickel mesh (46 mesh, stretched) was ultrasonically cleaned and dried, an excess amount of the slurry was manually coated, and then the slurry was coated on one side of the nickel mesh by a casting method, and then placed in an air atmosphere and placed in an oven at 150° C. for 10 minutes to obtain a blank (thickness of 0.64 mm);

[0045] (3) In an air atmosphere, the green embryo is heated to 350° C. at a rate of 60° C. / h and kept at this temperature for 30 minutes for debinding to obtain a pretreated green embryo;

[0046] (4) The pretreated blank is placed in an inert atmosphere for reduction high-temperature sintering, wherein the composition of the inert atmosphere is H2 / N2=3%, the sintering temperature is 850°C, and the insulation time is 10 minutes. After completion, an alkaline water hydrogen production anode is obtained.

[0047] Example 4

[0048] This embodiment provides a method for preparing an alkaline water hydrogen production anode, comprising the following steps:

[0049] (1) Commercially available ultrafine porous nickel powder Type 240 TM (particle size of 2.1-2.2 μm) and methyl cellulose are mixed and prepared into a slurry according to a conventional method; wherein the mass fraction of nickel powder in the slurry is 46%, the mass fraction of methyl cellulose is 3%, and the viscosity of the slurry is 30 Pa·S;

[0050] (2) After a nickel mesh (46 mesh, stretched) was cleaned and dried by ultrasonic wave, an excess amount of the slurry was manually coated, and then the slurry was coated on one side of the nickel mesh by casting, and then placed in an oven at 150° C. in an air atmosphere for 10 min to obtain a blank (thickness of 0.59 mm);

[0051] (3) In an air atmosphere, the green embryo is heated to 350° C. at a rate of 60° C. / h and kept at this temperature for 30 minutes for debinding to obtain a pretreated green embryo;

[0052] (4) The pretreated blank is placed in an inert atmosphere for reduction high-temperature sintering, wherein the composition of the inert atmosphere is H2 / N2=3%, the sintering temperature is 1050°C, and the insulation time is 10 minutes. After completion, an alkaline water hydrogen production anode is obtained.

[0053] Example 5

[0054] This embodiment provides a method for preparing an alkaline water hydrogen production anode, comprising the following steps:

[0055] (1) Commercially available ultrafine porous nickel powder Type 240 TM (particle size of 2.1-2.2 μm) and methyl cellulose are mixed and prepared into a slurry according to a conventional method; wherein the mass fraction of nickel powder in the slurry is 46%, the mass fraction of methyl cellulose is 3%, and the viscosity of the slurry is 30 Pa·S;

[0056] (2) After the nickel felt was cleaned and dried by ultrasonic wave, an excess amount of the slurry was manually coated, and then the slurry was coated on one side of the nickel mesh by casting, and then placed in an oven at 150° C. in an air atmosphere for 10 minutes to obtain a blank (thickness of 0.65 mm);

[0057] (3) In an air atmosphere, the green embryo is heated to 350° C. at a rate of 60° C. / h and kept at this temperature for 30 minutes for debinding to obtain a pretreated green embryo;

[0058] (4) The pretreated blank is placed in an inert atmosphere for reduction high-temperature sintering, wherein the composition of the inert atmosphere is H2 / N2=3%, the sintering temperature is 1050°C, and the insulation time is 10 minutes. After completion, an alkaline water hydrogen production anode is obtained.

[0059] Example 6

[0060] This embodiment provides a method for preparing an alkaline water hydrogen production anode, comprising the following steps:

[0061] (1) Commercially available ultrafine porous nickel powder Type 240 TM (particle size of 2.1-2.2 μm) and methyl cellulose are mixed and prepared into a slurry according to a conventional method; wherein the mass fraction of nickel powder in the slurry is 46%, the mass fraction of methyl cellulose is 3%, and the viscosity of the slurry is 30 Pa·S;

[0062] (2) After the nickel foam is cleaned and dried by ultrasonic wave, an excess amount of the slurry is manually coated, and then the slurry is coated on one side of the nickel mesh by casting, and then placed in an oven at 150° C. in an air atmosphere for 10 minutes to obtain a blank (thickness of 0.63 mm);

[0063] (3) In an air atmosphere, the green embryo is heated to 350° C. at a rate of 60° C. / h and kept at this temperature for 30 minutes for debinding to obtain a pretreated green embryo;

[0064] (4) The pretreated blank is placed in an inert atmosphere for reduction high-temperature sintering, wherein the composition of the inert atmosphere is H2 / N2=3%, the sintering temperature is 1050°C, and the insulation time is 10 minutes. After completion, an alkaline water hydrogen production anode is obtained.

[0065] Comparative Example

[0066] This embodiment provides a method for preparing an alkaline water hydrogen production anode, comprising the following steps:

[0067] (1) Commercially available ultra-fine porous nickel powder Type 255 TM (particle size of 2.2-2.8 μm) and methyl cellulose are mixed and prepared into a slurry according to a conventional method; wherein the mass fraction of nickel powder in the slurry is 54%, the mass fraction of methyl cellulose is 3%, and the viscosity of the slurry is 30 Pa·S;

[0068] (2) After a nickel mesh (46 mesh, stretched) was cleaned and dried by ultrasonic wave, an excess amount of the slurry was manually coated, and then the slurry was coated on one side of the nickel mesh by casting, and then placed in an oven at 150° C. in an air atmosphere for 10 min to obtain a blank (thickness of 0.70 mm);

[0069] (3) In an air atmosphere, the green embryo is heated to 350° C. at a rate of 60° C. / h and kept at this temperature for 30 minutes for debinding to obtain a pretreated green embryo;

[0070] (4) The pretreated blank is placed in an inert atmosphere for reduction high-temperature sintering, wherein the composition of the inert atmosphere is H2 / N2=3%, the sintering temperature is 1050°C, and the insulation time is 10 minutes. After completion, an alkaline water hydrogen production anode is obtained.

[0071] Analysis example

[0072] The anodes obtained from the embodiments and comparative examples were tested, and the porosity and adhesion strength of each group of sintered anodes were measured. The porosity was determined by cutting out a 33.5 mm × 15 mm sample, measuring the volume and weight of the sample, and subtracting the contribution of the metal strip in each sample. In the adhesion strength test, a 12 mm × 12 mm sample was cut out, and a 6 mm × 6 mm square aluminum column with a handle was bonded parallel to the top surface of the sample cutout, which was mounted on a ceramic substrate. All bonding was done with epoxy resin adhesive. The handle was connected to a tensile testing machine (an Instron universal testing machine was used in the present invention), and the normal force at the yield point when the handle was removed was recorded, and then divided by the area of ​​the sample handle to obtain the bonding strength between the sintered sample and the substrate. The data are shown in Table 1.

[0073] Table 1

[0074]

[0075] Table 1 (Continued)

[0076]

[0077]

[0078] When selecting the electrode carrier substrate material, it is necessary to comprehensively consider its catalytic activity, stability, cost and feasibility of the manufacturing process. Different substrates have different characteristics and need to be selected as needed. Specifically: Nickel felt may be superior to other materials in some properties, such as specific surface area, tensile strength and elongation, but its production cost is relatively high. The unique three-dimensional porous structure of nickel foam allows it to remain lightweight while also having a certain impact on its hardness. Porous stainless steel nickel-plated plate combines the high strength of stainless steel with the catalytic activity of nickel, has good corrosion resistance, can be used as a structural support and catalytic active layer, and reduces material costs, but high corrosion-resistant nickel coating is the key. Nickel mesh has higher electrical conductivity and mechanical strength, relatively low cost, easy processing and maintenance, and is widely used due to its cost-effectiveness and mature preparation process, but its surface area is relatively small and its catalytic efficiency is not as good as nickel felt and nickel foam.

[0079] In the comparative example, a nickel mesh was used as the substrate, Type 255 TMSintered onto a substrate as an active electrode. In Example 1, except for the different electrode sintering temperatures, other conditions remain unchanged. Compared with the comparative example, the sintering temperature in Example 1 is 700°C, and the thickness of the sintered embryo obtained is 0.68 mm, the porosity is 96.4%, and the substrate bonding strength is 95 kPa; the sintering temperature in Example 2 is 1350°C, and the thickness of the sintered embryo obtained is 0.34 mm, the porosity is 50.8%, and the bonding strength with the substrate is 4484 kPa. The sintering temperature plays a significant role in the sintering of the electrode and is an important condition for the electrode to obtain the required performance. At different sintering and infiltration temperatures, the quality of the sintered electrodes is different. From the results of the present invention, there is an inverse relationship between the strength and porosity of the sintered anode, and the sintering parameters need to be optimized to obtain the maximum porosity (which means using less nickel powder) and a relatively high bonding strength of the catalytic substrate / sintered anode. When the sintering temperature is too low (such as Example 1, the sintering temperature is 700°C) or too high (such as Example 2, the sintering temperature is 1350°C), a usable electrode cannot be obtained. In the process of hydrogen production by electrolysis of water, the nickel mesh is used as a catalyst carrier, and the bonding force between it and the catalyst is affected by the diffusion process, which in turn affects the performance of the entire electrode. The nickel-nickel diffusion coefficient usually increases with increasing temperature, because high temperature provides more thermal energy, making it easier for atoms to jump to adjacent vacancies for diffusion. When the temperature is too low, although the electrode has a higher porosity, the strength between it and the carrier is much lower than that of the comparative example, and the catalyst may fall off from the surface of the nickel mesh, resulting in a reduction in active sites, thereby reducing the production of hydrogen. Increasing the sintering temperature will increase the adhesion between the nickel powder and itself and the substrate, but it may also cause structural collapse, forming a catalyst layer with too low porosity, and reducing the active sites of the electrode. The experimental results show that the sintered nickel electrode is kept warm for 5 minutes, and the furnace door is slightly opened to allow the porcelain sheet and the electrode to cool with the furnace. The cooling rate is appropriate to obtain a nickel electrode with good ohmic contact. Before sintering, the nickel powder particles are covered by the gas adsorbed, the oxide film and the binder film added to the slurry, and the metal contact between the particles is very small. After sintering, the gaps between the particles disappear, which increases the contact surface of the powder particles and forms a continuous conductive network, which can make the nickel electrode have good conductivity. The film sintered at 1050°C (Example 4) is denser and has better adhesion than the film sintered at 850°C (Example 3), indicating that the surface performance of the film obtained at 1050°C is good.

[0080] The mechanical strength of the nickel blank and its adhesion to the substrate are critical to battery reliability and to reducing scrap rates during electrode manufacturing. First, the nickel blank must withstand rigorous chemical, thermal, and mechanical cycles during repeated chemical impregnation to fill its porous active mass. During this stage, any breakage or detachment of the blank from the substrate will result in failure and scrap of the electrode. The battery electrodes are then subjected to harsh chemical environments (e.g., KOH), cyclic deformations associated with the charge and discharge processes, and thermal fluctuations. Typically, the volume of the blank after sintering is about one-third of the volume of the initial slurry, e.g., Figure 1 As shown. During drying and sintering, such great compaction generates mechanical stresses that are considered triaxial in nature. Since the substrate is a thin layer (<1 mm), the structural gradients and stresses perpendicular to the substrate surface are negligible. However, stresses acting in the plane of the substrate may cause bending, mechanical degradation and cracking of the coating during drying, sintering and in use. Cohesive covalent bonding through the slurry layers on the opposite sides of the substrate is also responsible for the integral adhesion of the blank to the substrate.

[0081] In Examples 3 and 4, Type 240 is selected. TM Nickel powder is used as a catalyst. In order to keep the viscosity of the configured slurry consistent with that of the comparative example, the content of nickel powder is reduced from 54% to 46%. The sintering conditions in Example 3 are consistent with those of the comparative example. Compared with the comparative example, under the same sintering conditions, the porosity of the electrode is higher than that of the comparative example, and the bonding strength with the substrate is lower than that of the comparative example. In Example 4, the sintering temperature is increased to 1050°C. Compared with Example 3, the porosity of the electrode is slightly reduced, but the bonding strength with the substrate is significantly improved. Type 240 is selected. TM Using nickel powder as electrode raw material can reduce the nickel content by 85%, while maintaining high porosity and good bonding strength (Example 4), indicating that the surface performance of the film obtained under this condition is good. TM In comparison, Type 240 TM Nickel powder has a smaller particle size and lower density, so it is speculated that Type 240 TM Nickel powder particles have more needle-like structures.

[0082] The slurry preparation conditions, coating and sintering conditions in Examples 5 and 6 are consistent with those in Example 4, and nickel felt and nickel foam are used as electrode carriers, respectively. The obtained electrode thickness and porosity are basically similar to those in Example 4, but the bonding strength between the electrode and the carrier is enhanced compared with that in Example 4. The reason may be that nickel felt and nickel foam have a denser surface structure than nickel mesh, there are more contact points between nickel powder and the carrier, and the particles that penetrate into the porous carrier are closer to each other, forming an interlocking structure with the particles on the opposite side. In most cases, the contribution of this cohesive bonding is far greater than any adhesive bonding formed between the porous nickel structure and the catalyst layer substrate.

[0083] The electrolytic cell composed of the anode electrode and the nickel foam cathode electrode prepared in Examples 4, 5, 6 and the comparative example was tested for loading. The linear sweep voltammetry method was adopted, and the electrochemical workstation was Solartron Energylab XM as the constant current source. The linear scan range was 1-2V, the scan rate was 10mV / s, the electrolyte solution was 30% potassium hydroxide solution, the electrolytic cell temperature was 80°C, and the electrolyte flow rate was 75mL / min. The evaluation standard was the current density corresponding to 2V. The test results are shown in Figure 2 As shown: Compared with the anodes of Examples 4, 5, and 6, the performance of the electrolytic cell composed of the anode of the comparative example is 7877A / m 2 @2V, which is the worst performance among all samples. The electrolytic cell performances of the anode compositions of Examples 5, 6, and 4 are 12169A / m 2 、11934A / m 2 、11034A / m 2 The performance of the electrolyzer is not only related to the preparation process of the electrode material, but also to the selection of the catalyst layer carrier. The electrodes prepared with nickel felt and nickel foam carriers have the best performance, mainly because their surfaces have a relatively dense structure compared to the nickel mesh and have relatively more active sites. On the other hand, since the surfaces of nickel felt and nickel foam are relatively flat, the nickel catalyst layer is relatively uniform, and the catalyst layer has a better interlocking structure, which increases the activity of the electrode.

[0084] The above is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any person skilled in the art can easily think of changes or substitutions within the technical scope disclosed by the present invention, which should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.

Claims

1. A method for preparing an alkaline water hydrogen production anode, characterized in that: The steps include: (1) mixing ultrafine porous nickel powder and methyl cellulose to prepare a slurry; (2) cleaning and drying the substrate, then coating the slurry on one side of the substrate by casting, and finally drying to obtain a blank; (3) heating the green embryo to remove binder and obtain a pretreated green embryo; (4) Sintering the pretreated blank to obtain the alkaline water hydrogen production anode.

2. The method for preparing an alkaline water hydrogen production anode according to claim 1, characterized in that: In step (1), the particle size of the ultrafine porous nickel powder is 2.1 to 2.8 μm.

3. The method for preparing an alkaline water hydrogen production anode according to claim 1, characterized in that: In step (1), in the slurry, the mass fraction of ultrafine porous nickel powder is 15-70%, and the mass fraction of methyl cellulose is 3-4%; And / or, the viscosity of the slurry is 30-35 Pa·S.

4. The method for preparing an alkaline water hydrogen production anode according to claim 1, characterized in that: In step (2), the substrate is one of nickel mesh, nickel felt, nickel foam, perforated nickel belt, nickel-plated metal porous plate, and nickel-plated metal porous belt.

5. The method for preparing an alkaline water hydrogen production anode according to claim 1, characterized in that: In step (2), the drying method is: drying in an air atmosphere at 150-160° C. for 10-15 minutes.

6. The method for preparing an alkaline water hydrogen production anode according to claim 1, characterized in that: In step (3), the heating method is: in an air atmosphere, the temperature is raised to 350-360°C at a rate of 60°C / h, and the temperature is kept for 30-40 minutes.

7. The method for preparing an alkaline water hydrogen production anode according to claim 1, characterized in that: In step (4), the sintering method is: sintering at 700-1350° C. for 10-15 minutes in an inert atmosphere.

8. The method for preparing an alkaline water hydrogen production anode according to claim 7, characterized in that: The inert atmosphere is a mixed gas of hydrogen and nitrogen, and the volume ratio of hydrogen to nitrogen is 3:

100.

9. The alkaline water hydrogen production anode obtained by the preparation method according to any one of claims 1 to 8.

Citation Information

Patent Citations

  • Anion-exchange membrane water electrolysis cathode electrode material under high current density and macro preparation method and application of anion-exchange membrane water electrolysis cathode electrode material

    CN118480810A

  • Nickel-molybdenum electrode with high activity and high stability under high current density as well as preparation method and application of nickel-molybdenum electrode

    CN118639258A

  • Metal composite electrode, method for preparing metal composite electrode through thermal spraying and application

    CN118653173A